AB0591 Organ Damage Evaluation and Risk Factors in a Cohort of 511 Sle Patients. (9th June 2015) - Taraborelli, M.; Martinazzi, N.; Lazzaroni, M.G.; Andreoli, L.; Fredi, M.; El Masri, Y.; Cartella, S.; Cavazzana, I.; Taglietti, M.; Frassi, M.; Franceschini, F.; Tincani, A.
Abstract : Background: Systemic lupus erythematosus (SLE) is still burdened by a significant morbidity and mortality. Objectives: To determine the prevalence of organ damage, with related risk factors, and mortality in a cohort of SLE patients. Methods: The clinical records of patients fulfilling the American College of Rheumatology (ACR) criteria for SLE, followed for at least 1 year in our center were retrospectively reviewed. Organ damage was assessed by the Systemic Lupus International Collaborating Clinics/ACR Damage Index (DI) at 1 year after diagnosis and then every 5 years, from the beginning until the end of the follow-up in our center. Disease activity was measured by the SLE Disease Activity Index (SLEDAI) 2K at the beginning of the follow-up. The comparison of characteristics between patients with and without damage at the end of their follow-up was performed by the Chi Square's, Fisher's exact and Student's t test as appropriate; p<0.05 was considered significant. Results: This study included 511 SLE patients (92% females, 95% Caucasians), followed in our Unit between 1972 and 2014, with a mean age at diagnosis of 33 years (±13) and a mean disease duration at the end of the follow-up of 16 (±9) years. One year after diagnosis 40% of patients with measurable DI (n=400) had accrued some damage and its prevalence gradually increased over time (Table I ). At 1 year ocular (13%), central nervous system (12%) and skin (8%) damage were the most frequent whereas ocular, skin and musculoskeletal were the most frequent sites of damage (40%) at 35 years. Different features were significantly associated to damage (Table II ). The main causes of death in 35 patients (7%) were cancer (33%) and organ failure (22%) after a mean disease duration of 13 years. Conclusions: The organ damage that accumulates over time in SLE is partly linked to disease activity, partly defined by clinical profiles (neuro-SLE, renal disease and Antiphospholipid Syndrome) that may require aggressive treatments. New, more effective and less toxic drugs could limit the progression of this process. Disclosure of Interest: None declared